Association between exposure to earthquake in early life and diabetes mellitus incidence in adulthood with the modification of lifestyles: Results from the Kailuan study - Shui, Xinying; Zhao, Lei; Li, Wenli; Jia, Yaning; Liu, Ziquan; Li, Chen; Yang, Xueli; Huang, Haoran; Wu, Shouling; Chen, Shuohua; Gao, Jingli; Li, Xiaolan; et al. (Frontiers in Pediatrics, 2022)
Background: Exposure to disasters in early life may induce lifetime health risk, but investigation on earthquake exposure and DM in later life is still limited. The aim of the current study is to evaluate the association between exposure to the Tangshan Earthquake in early life and diabetes mellitus (DM) incidence in adulthood, and explore the modification of lifestyles on DM development. Methods: Participants who were free of DM at baseline were included in this study. All participants were divided into fetal-exposed, infant-exposed, early childhood-exposed and nonexposed group. The effect of earthquake exposure on DM and modification of lifestyles were examined by multivariable-adjusted Cox proportional hazard model. Results: The exposed group had a higher risk of DM than nonexposed group, especially in infant-exposed and early childhood-exposed group, with hazard ratio (HR) of 1.62 (95% confidence intervals [CI], 1.21-2.17) and 1.46 (95% CI, 1.06-1.99), respectively. After stratifying by lifestyles, a significant modification was observed in alcohol consumption. Conclusions: Exposing to earthquake in early life could increase DM incidence in later life, and alcohol consumption might modify the effect of earthquake exposure on DM development. More attention should be paid on the preventions of DM among adults who exposed to earthquake in their early life.